Application Of Expert System To Diagnose Pests And Diseases In Coffee Plant Using Web-Based Naïve Bayes: Application Of Expert System To Diagnose Pests And Diseases In Coffee Plant Using Web-Based Naïve Bayes - Rafi Syahputra; Agung Triayudi; Ira Diana Sholihati (Institute of Computer Science (IOCS), 2020)
Every year the demand for coffee in Indonesia is increasing, this is because coffee is a plantation that has long been cultivated and is one of the livelihoods of the people in Indonesia. Moreover, the high level of exports makes coffee plants very influential for the country's economy and foreign exchange. Besides the many needs, the spread of pests and diseases in coffee plants is one of the problems that must be addressed immediately. Based on the existing problems, the author finally designed an expert system created to diagnose coffee plant diseases using The Naïve Bayes method, which is one of the simple classification methods which in return can give a probability value for each disease that is raised. This system can help coffee planters to identify diseases in coffee plants. The test results in this study were able to produce an accuracy level of 92% so that this system can be used to diagnose pests and diseases in coffee plants.